PARTICIPATION OF CITIZENS IN ENVIRONMENTAL DECISION-MAKING PROCESSES (American Journal of Technology and Applied Sciences, 2024)
This article discusses the ecological rights of citizens, ecological interests, the basis and importance of their participation in environmental decision-making, as well as the solutions and foundations of ensuring the rational use of natural resources.